O ensino do cálculo diferencial e integral na perspectiva da Sequência Fedathi: caracterização do comportamento de um bom professor - Menezes, Daniel Brandão (2018)
The courses in the area of Exact Sciences, particularly as Undergraduate Mathematics in Ceará, have already done several works with a Differential and Integral Calculus, regarding the methodological aspects developed in the training sessions that still did not have points of dissatisfaction, reason for withdrawal and disapproval on the part of the students. Faced with this problem, this thesis deals with a research based on its methodology of teaching and teaching The discipline of Advanced Thought (Master of Science) aims to investigate its relationship with different levels of education. (CDI) of the students of a study group of the State University of Vale do Acaraú, responding in a didactic way to a learning of concepts and a proof, in particular, of the contents of a class of variance, and how a characterization of the teacher in support of these concepts. As a preliminary theoretical support, the studies of the Fedati Sequence, Theory of Advanced and Advanced Computing Thinking (Geogebra) for development with the improvement of the teaching-learning process were included. Then, to reach the objectives, the didactic sessions were worked with the Fedathi Sequence as methodology for elaboration and conduction in the teaching of the content. The research is qualitative in nature, outlined as a participant and, in addition, followed the scientific method Fedathi Sequence, described and studied in the course of the work; as field and subjects of the investigation, the essay was outlined in a group of studies created in the course of Mathematics of the State University Vale of Acaraú and the subjects were the enrolled students and the teacher who mediated the meeting. In the course of experimentation, the research questions were answered and collected results that served as a basis for the classification of good teachers and good students. The research methodology proved to be a rigid method to be promoted scientifically, correctly directing each stage of the experiment and the methodological instruments necessary for the collection and collection of data. In the course of the practices and consequent analysis, it was possible to establish a relationship between the SF and the PMA in the tests that were applied with the students. In addition, it was concluded that the use of the computational resource was beneficial to the understanding of the contents, with the contextualized questions used as problems in the experience of the Position Taking, that is, it contributed to demand comprehension for the teaching of Differential Calculus and Integral, in addition to developing advances in research in Mathematics Education and, above all, how the teaching behavior influenced the students' emotions in relation to Mathematics and in conducting the experience of the Fedathi Sequence.